2014
DOI: 10.1111/1365-2435.12383
|View full text |Cite
|
Sign up to set email alerts
|

Female anoles retain responsiveness to testosterone despite the evolution of androgen‐mediated sexual dimorphism

Abstract: Summary1. The evolution of sexual dimorphism presents a challenge because males and females must express two phenotypes from the same underlying genome. In vertebrates, one solution to this challenge is to link the expression of shared traits to sex steroids. However, even 'male-biased' steroids such as testosterone (T) circulate at biologically significant levels in females, raising the question of whether sexual dimorphism evolves not only through the coupling of trait expression to T in males, but also thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 93 publications
5
43
0
Order By: Relevance
“…T, DHT, E2), which may be facilitated via changes in ovarian steroid production during the pre-nuptial molt. Although a coupling of sexual dimorphism to sex differences in adult androgen secretion may explain the evolution of sex differences in many traits (Cox et al, 2015), our results implicate a role for additional actions of female hormones and non-hormonal mechanisms in regulating dimorphic expression of complex, multi-component traits.…”
Section: Discussionmentioning
confidence: 64%
“…T, DHT, E2), which may be facilitated via changes in ovarian steroid production during the pre-nuptial molt. Although a coupling of sexual dimorphism to sex differences in adult androgen secretion may explain the evolution of sex differences in many traits (Cox et al, 2015), our results implicate a role for additional actions of female hormones and non-hormonal mechanisms in regulating dimorphic expression of complex, multi-component traits.…”
Section: Discussionmentioning
confidence: 64%
“…The reasons for this apparently general pattern of asymmetry in B are not well understood, but may include prior effects of sex‐specific selection in combination with mechanisms such as genomic imprinting, sex linkage and sex‐biased expression of the genes underlying dimorphic phenotypes (Wyman et al ., ). Although our study does not directly address any of these potential mechanisms, previous experiments have shown that dewlap size and coloration are strongly responsive to testosterone in brown anoles (Cox et al ., , ). Sex‐biased modifiers of gene expression, such as testosterone, may contribute not only to the phenotypic expression of sexual dimorphism in dewlap size and colour, but also to the corresponding reduction of between‐sex genetic correlations (Cox et al ., ) and the creation of sex‐specific patterns of phenotypic and genetic integration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, the induction of male-typical growth by exogenous testosterone in non-OVX females in these two geckos (Kubicǩa et al, 2013;Starostová et al, 2013) as well as in other squamates (mostly studied in female-larger species: reviewed in Starostová et al, 2013; but also recently in the male-larger anole A. sagrei : Cox et al, 2015) still leaves open the possibility that testicular androgens can cause growth masculinization. This suggestion was based on the parsimonious expectation that elevated levels of androgens in females should have the same effect in both sexes and therefore influence growth in males and females in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…However, and at first sight paradoxically, the induction of maletypical levels of circulating testosterone in females led to a 'masculinization' of growth in both female-larger and male-larger lizard species. Non-ovariectomized (non-OVX) females treated by exogenous testosterone attained larger, male-like final snout-vent length (SVL) in the male-larger lizard species (Starostová et al, 2013;Cox et al, 2015), while exogenous testosterone acted negatively on the growth and final SVL in females of the femalelarger gecko (Kubicǩa et al, 2013). We suggest that the discrepancy between the effects of testosterone in males and females can be explained by the scenario where the development of SSD does not require masculinization by male gonadal androgens, but rather feminization by female gonadal hormones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation